2008
DOI: 10.1111/j.1460-9592.2008.02529.x
|View full text |Cite
|
Sign up to set email alerts
|

Determining the accuracy of caudal needle placement in children: a comparison of the swoosh test and ultrasonography

Abstract: Ultrasonography is superior to the 'swoosh' test as an objective confirmatory technique during caudal block placement in children. We found the presence or absence of turbulence during injection within the caudal space to be the best single indicator of caudal success. We think ultrasonography should be used, if available, when teaching this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 21 publications
(24 reference statements)
0
37
0
5
Order By: Relevance
“…The PNB set contained 6 RCTs 2Y7 and 6 case series, 8Y13 whereas the neuraxial set contained 1 RCT, 14 1 comparative study, 15 and 10 case series. 16Y25 A modified PRISMA flow diagram (designed for reporting of systematic reviews) is included in Figure 1 (www.prisma-statement.org).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PNB set contained 6 RCTs 2Y7 and 6 case series, 8Y13 whereas the neuraxial set contained 1 RCT, 14 1 comparative study, 15 and 10 case series. 16Y25 A modified PRISMA flow diagram (designed for reporting of systematic reviews) is included in Figure 1 (www.prisma-statement.org).…”
Section: Resultsmentioning
confidence: 99%
“…23 The relative clarity of the images, although illustrated as high, was not reported except for that of the sacrococcygeal membrane (which was not easily seen in 1 patient). Without comment on the visibility of the dural sac in other reports of ultrasound use for caudal blocks in children, 15,21 it is not possible to make any recommendation at this time.…”
Section: Neuraxial Anesthesiamentioning
confidence: 97%
“…The use of epidural electrical simulation may be used in conjunction with ultrasound guidance to ensure proper needle placement within the caudal epidural space. When compared to the swoosh test for confirming caudal epidural placement, investigators found real time ultrasonography to have significantly higher sensitivity and negative predictive value (Raghunathan et al, 2008). The low negative predictive value may be explained in part by the older age of the patients (5-8 yrs).…”
Section: Outcome and Discussionmentioning
confidence: 99%
“…Current research supports the use of ultrasound imaging in both the transverse (Raghunathan et al, 2008;Schwartz et al, 2008) and longitudinal (Roberts & Galvez, 2005;Park et al, 2006) planes to guide needle placement during a caudal block. For the transverse technique, the probe was placed just cephalad to the point of injection.…”
Section: Techniquementioning
confidence: 99%
“…Recently, a retrospective observational study of caudal injections in 83 pediatric patients was conducted to compare the accuracy of caudal needle placement with the Bswoosh[ test, 2-dimensional transverse ultrasonographic evidence of turbulence within the caudal space, and color flow Doppler. 60 The authors concluded that ultrasonography is superior to the swoosh test as an objective confirmatory technique during caudal block placement in children. They found the presence or absence of turbulence during injection within the caudal space to be the best single indicator of block success.…”
Section: Literature Review Of Us-guided Caudal Epidural Injectionsmentioning
confidence: 98%